A study of responsibility and performance of project management consultant (PMC) in the construction industry in Malaysia (residential project) - Syahrulhazwan , Shamsuddin (2013)
Nowadays, abandoned housing projects taking place in Malaysia was a major problem that is getting scabby in the residential industry. It is a residential project where construction or development phase of the project has been delayed or stopped in an unreasonable time frame. Among the causes of abandoned housing projects are; financial flow problems developers; Problem disputes between landlords and developers; studies were not conducted detailed market; technical problem site; squatter problem, and the company's internal problems. To accommodate the national rapid economic expansion demands for building and infrastructure, new model or method must be introduced to replace the regular practice. Thus before these things become more severe it is better to take appropriate action. In this thesis proposes to appoint a Project Management Consultant by each contractor or developer site before work on the run. With this in hope every residential project can be developed without any delay and cost to the developer. Project management consultant is one of the way to overcome the problem arises. Project management consultant is an organization that helps client or owner to supervise their construction, so that the construction done without any delays or overruns cost due to poor management handling materials, tools and labour. The use of Project management consultant must become a mandatory requirement for five kinds of projects, namely national key projects, large-scale public projects, large-scale housing projects, projects funded or aided by foreign loans and special projects.